2023
DOI: 10.3390/photonics10080951
|View full text |Cite
|
Sign up to set email alerts
|

An Ytterbium-Doped Narrow-Bandwidth Randomly Distributed Feedback Laser Emitting at a Wavelength of 976 nm

Danila A. Davydov,
Andrey A. Rybaltovsky,
Svetlana S. Aleshkina
et al.

Abstract: All-fiber, polarization maintaining, narrow-bandwidth, Yb-doped fiber lasers with randomly distributed feedback operated near 976 nm were realized for the first time. It was shown that the laser operated in a single, longitudinal mode regime during intervals of a few seconds. At other times, the laser generated a few longitudinal modes, but its bandwidth was always below the resolution of the optical spectrum analyzer (0.02 nm). The linewidth of each single longitudinal mode of the laser was estimated to be be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Firstly, lasers at different emission wavelengths have been achieved. Danila et al demonstrated a 976 nm Ytterbium-doped narrowbandwidth randomly distributed feedback laser [1]. Lasers that are operated at 1.5 µm wavelength have been obtained via different methods, such as random laser cavity [2], distributed Bragg reflector laser cavity [3], passive mode locking based on a saturable absorber [4], Brillouin random lasing oscillation, and four-wave mixing [5].…”
mentioning
confidence: 99%
“…Firstly, lasers at different emission wavelengths have been achieved. Danila et al demonstrated a 976 nm Ytterbium-doped narrowbandwidth randomly distributed feedback laser [1]. Lasers that are operated at 1.5 µm wavelength have been obtained via different methods, such as random laser cavity [2], distributed Bragg reflector laser cavity [3], passive mode locking based on a saturable absorber [4], Brillouin random lasing oscillation, and four-wave mixing [5].…”
mentioning
confidence: 99%